Dynamically generated synthetic electric fields for photons - Zapletal, Petr; Walter, Stefan; Marquardt, Florian (Physical Review A, 2019)
Static synthetic magnetic fields give rise to phenomena including the Lorentz force and the quantum Hall effect even for neutral particles, and they have by now been implemented in a variety of physical systems. Moving toward fully dynamical synthetic gauge fields allows, in addition, for backaction of the particles' motion onto the field. If this results in a time-dependent vector potential, conventional electromagnetism predicts the generation of an electric field. Here, we show how synthetic electric fields for photons arise self-consistently due to the nonlinear dynamics in a driven system. Our analysis is based on optomechanical arrays, where dynamical gauge fields arise naturally from phonon-assisted photon tunneling. We study open, one-dimensional arrays, where synthetic magnetic fields are absent. However, we show that synthetic electric fields can be generated dynamically. The generation of these fields depends on the direction of photon propagation, leading to a mechanism for a photon diode, inducing nonlinear unidirectional transport via dynamical synthetic gauge fields.
CRIS-Team WoS Importer:2019-08-16